Petrol production resource-efficiency increase with the help of mathematical modeling method; IFOST 2012; Vol. 1 - Gyngazova M. S. Mariya Sergeevna (Section 1. Chemical engineering and "Green technology", 2012)
Catalytic reforming is one of the most important processes for high octane gasoline manufacture and aromatic hydrocarbons production. There are several ways of this process modernization. It is effective to use mathematical modeling method to examine all possible variants because it requires low time and financial investments. In this work we analyzed the set of possible reactions, proposed kinetic model for catalytic reforming process, calculated thermodynamic and kinetic parameters, investigated catalyst layer hydrodynamics. A mathematical model for a moving-bed catalytic reforming reactor taking into account activity and circulating factor of the catalyst was presented. The model allows analyzing various variants of process modernization and can help to find optimal operation regimes.